Depression among adult patients with primary brain tumour: a cross-sectional study of risk factors in a low–middle-income country. Issue 9 (9th September 2020) - Pidani, Anum Sadruddin; Siddiqui, Amna Rehana; Azam, Iqbal; shamim, Muhammad Shahzad; Jabbar, Adnan Abdul; Khan, Shameel
Abstract : Objective: The prevalence of depression among patients with primary brain tumour ranges from 15% to 40% globally. Several individual and clinical factors contribute to the development of depression. However, their association with depression in Pakistani setting has not yet been assessed. Thus, we aim to study the factors associated with depression among adult patients with primary brain tumour at a tertiary care hospital in Karachi, Pakistan. Study design: A prospective cross-sectional study. Setting: This study was conducted at a tertiary care hospital of Karachi, Pakistan. Participants: This study included 132 patients with confirmed diagnosis of primary brain tumour (initially diagnosed on MRI of the brain with contrast and later confirmed on histology of surgical specimen) in various stages of treatment. Primary outcome: The primary outcome of this study was to assess depression and its associated factors among adult patients with primary brain tumour. Depression was assessed using a validated screening tool Patient Health Questionnaire-9 (PHQ-9). Scores of 10–27 on PHQ-9 were indicative of screen positive for depressive symptoms. A set of the structured pre-tested questions was used to evaluate patient-related, tumor-related and treatment-related factors. Results: Fifty-one (39%, CI: 33.33–46.94) patients in our study screened positive for depressive symptoms on PHQ-9. There was a significant association between depressive symptoms and Karnofsky Performance Scores (KPS) (prevalence ratio: 3.25 and CI: 1.87–5.62) after controlling covariates. Propensity scores predicted a positive association between KPS (functional status) and unemployment, treatment stage, and tumour recurrence. Tumor-related and treatment-related factors including tumour grade, location, type and hemispheric lateralisation were found insignificant. Conclusion: Depression is common in patients with primary brain tumour. Impaired functional status has a direct impact on depression in these patients. Incorporating the psychosocial domain earlier in the course of treatment needs to be considered for better neuro-oncology management of patients with primary brain tumour.